Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
`M+N`
`=2x^{2}-2xy-3y^{2}+1+x^{2}-2xy+3y^{2}+1`
`=(2x^{2}+x^{2})-(2xy+2xy)+(3y^{2}-3y^{2})+1+1`
`=3x^{2}-4xy+2`
`M-N`
`=2x^{2}-2xy-3y^{2}-(x^{2}-2xy+3y^{2}+1)`
`=2x^{2}-2xy-3y^{2}-x^{2}+2xy-3y^{2}-1`
`=(2x^{2}-x^{2})+(2xy-2xy)-(3y^{2}+3y^{2})+1-1`
`=x^{2}-6y^{2}
![](https://rs.olm.vn/images/avt/0.png?1311)
Do \(x+y-2=0\Leftrightarrow x+y=2\Leftrightarrow x-2=-y\)
\(N=x^2\left(x-2\right)-xy^2+2xy+2\left(x+y\right)-2\)
\(=-x^2y-xy^2+2xy+2.2-2=-xy\left(x+y\right)+2xy+2=-2xy+2xy+2=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1
a)M+N=\(x^2y+xy^2-5x^2y^2+x^3+x^3+xy+3xy^2-x^2y+x^2y^2\)
=4xy2-4x2y2+2x3+xy
b)M-N=\(x^2y+xy^2-5x^2y^2+x^3-x^3-xy-3xy^2+x^2y-x^2y^2\)
=\(2x^2y-2xy^2-xy-6x^2y^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) N=-2x2+3xy+3x2-3y-1
=-2x2+3x2+3xy-3y-1
=x2+3xy-3y-1
=>M+N=(x2+2xy+y-1)+(x2+3xy-3y-1)
=x2+2xy+y-1+x2+3xy+-3y-1
=x2+x2+2xy+3xy+y-3y-1-1
=2x2+5xy-2y-2
b)M-N= (x2+2xy+y-1)-(x2+3xy-3y-1)
=x2+2xy+y-1-x2-3xy+3y+1
=x2-x2+2xy-3xy+y+3y-1+1
=-xy+4y
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) A = M + N = ( 2x2y - xy2 + 3x - 2y ) + ( 2xy2 - 2x2y - 5x + 2y )
= 2x2y - xy2 + 3x - 2y + 2xy2 - 2x2y - 5x + 2y
= ( 2x2y - 2x2y ) + ( -xy2 + 2xy2 ) + ( 3x - 5x ) + ( - 2y + 2y )
= 0 + ( -1 +2 ) xy2 + ( 3 - 5 )x + 0
= xy2 - 2x
Vậy A = M + N = xy2 - 2x
B = N - M = 2xy2 - 2x2y - 5x + 2y - ( 2x2y - xy2 + 3x - 2y )
= 2xy2 - 2x2y - 5x + 2y - 2x2y + xy2 - 3x + 2y
= ( 2xy2 + xy2 ) + ( -2x2y - 2x2y ) + ( - 5x - 3x ) + ( 2y + 2y )
= ( 2 + 1 )xy2 + ( -2 - 2 )x2y + ( - 5 - 3 )x + ( 2 + 2 )y
= 3xy2 - 4x2y - 8x + 4y
Vậy B = 3xy2 - 4x2y - 8x + 4y
![](https://rs.olm.vn/images/avt/0.png?1311)
M=x^3+x^2.y-2x^2-xy-y^2+3y+x-1
=> M=x^2(x+y-2)-(xy+y^2-2y)+(y+x-1) = 0- y(x+y-2)+1=1
N=x^3-2x^2-xy^2+2xy+2y+2x-2
=> N= 2(x+y-1)+x(x^2-y^2)-2x(x-y)=2+x(x+y)(x-y)-2x(x-y)=2+(x^2+xy-2x)(x-y)=2+x(x+y-2)(x-y)=2+0=2(vì x+y-2=0)
M=(x^3+x^2y-2x^2)-(xy+y^2-2y)+(x+y-2)+1
=x^2(x+y-2)-y(x+y-2)+(x+y-2)+1
=x^2.0-y.0+0+1=1
N=x^3-2x^2-xy^2+2xy+2y+2x-2+x^2y-x^2y+2-2
=(x^3+x^2y-2x^2)-(x^2y+xy^2-2xy)+(2x+2y-4)+2
=x^2(x+y-2)-xy(x+y-2)+2(x+y-2)+2
=x^2.0-xy.0+2.0+2=2
Ta có : m + n hay \(2x^2-xy-3y^2+1+x^2-2xy+3y^2-1\)
\(m+n=3x^2-3xy\)
m - n hay \(2x^2-xy-3y^2+1-x^2+2xy-3y^2+1\)
\(m-n=x^2+xy-6y^2+2\)